Research-based Cooperative Learning in Higher Education - M.C. Saavedra Serrano (Universitat Politècnica de València, 2018)
This  article  shows  the  results  of  an educational  research  that  explores  the effects of a teaching innovation strategy on  the  learning  level  of  students  of some taxation subjects in the Law and Business  Management  degrees.  This strategy  is  implemented  through  an activity that combines two participatory methodologies, cooperative learning and research-based  learning.  Students  are requested to carry out a research project in small groups on taxation in an international context, complying with the standards of the scientific method. In order to analyze the  influence  of  the  teaching  strategy on the students learning level, a quasi-experimental research design is used with groups that have been formed academically. In addition, to contrast the main hypothesis of this study -the development in team of a research project enhances the students learning level to a greater extent than other activities not based on research-, are compared the post-test measures of the dependent variable (learning level) of both students groups, experimental and control, through the mean difference test. Likewise, this study examines, through an ad hoc questionnaire, the assessment of students about their learning experience and the competencies and skills that they have acquired with the activity, as for example teamwork and information management.